2009
DOI: 10.1111/j.1471-4159.2009.06330.x
|View full text |Cite
|
Sign up to set email alerts
|

The neurokinin‐1 receptor modulates the methamphetamine‐induced striatal apoptosis and nitric oxide formation in mice

Abstract: ,Met (O 2 ) 11 ] substance P; SST, somatostatin; TUNEL, terminal deoxyncleotidyl transferase-mediated dUTP nick end labeling. AbstractIn a previous study we showed that pharmacological blockade of the neurokinin-1 receptors attenuated the methamphetamine (METH)-induced toxicity of the striatal dopamine terminals. In the present study we examined the role of the neurokinin-1 receptors on the METH-induced apoptosis of some striatal neurons. To that end, we administered a single injection of METH (30 mg/kg, i.p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 58 publications
0
30
0
1
Order By: Relevance
“…Clearly, studies with strict control over potential contributing factors allowing for systematic independent and coordinate manipulation of the factors will be necessary to fully understand the process by which METH induces DA neurotoxicity. Furthermore, we cannot exclude a role of NO in striatal-efferent neuron toxicity observed in some models of METH-induced neurotoxicity (Zhu et al, 2009). Although the necessity of NO for METH-induced DA neurotoxicity remains in question, it is clear from the present findings that administration of a binge regimen of METH increases NO production.…”
Section: Discussionmentioning
confidence: 96%
“…Clearly, studies with strict control over potential contributing factors allowing for systematic independent and coordinate manipulation of the factors will be necessary to fully understand the process by which METH induces DA neurotoxicity. Furthermore, we cannot exclude a role of NO in striatal-efferent neuron toxicity observed in some models of METH-induced neurotoxicity (Zhu et al, 2009). Although the necessity of NO for METH-induced DA neurotoxicity remains in question, it is clear from the present findings that administration of a binge regimen of METH increases NO production.…”
Section: Discussionmentioning
confidence: 96%
“…The excessively high levels of extracellular dopamine induced by METH initiate a neurotoxic cascade producing free radicals and quinones that are damaging to proteins (Fornstedt and Carlsson, 1989; Hastings et al, 1996). The protracted overflow of dopamine induced by METH promotes the overflow of the excitotoxic transmitter glutamate (Nash and Yamamoto, 1992), nitric oxide production (Taraska and Finnegan, 1997; Zhu et al, 2009), microglial activation (LaVoie et al, 2004; Thomas et al, 2004), and bioenergetic compromise due to mitochondrial dysfunction (Chan et al, 1994; Brown and Yamamoto, 2003). The neurotoxic state induced by METH causes pre-synaptic neural damage including reduction of dopamine transporter function (Fleckenstein et al, 1997), oligomerization of the transporter (Baucum et al, 2004), decreased vesicular transporter function (Fleckenstein et al, 2003), inhibition of tyrosine hydroxylase activity (Hotchkiss et al, 1979), and protein levels (Yu et al, 2004), decreased tissue dopamine content (Wagner et al, 1980) and degeneration of striatal dopamine terminals (Ricaurte et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence implicating nitric oxide production in the striatal METH-induced neural damage accrues from pharmacological studies demonstrating that antagonists of neuronal nitric oxide synthase protect the striatum from METH (Itzhak and Ali, 1996; Itzhak et al, 2000), moreover, mice lacking the neuronal nitric oxide synthase gene show partial resistance to METH (Imam et al, 2001). Our laboratory has shown that the METH-induced elevation of striatal 3-nitrotyrosine (an indirect index of nitric oxide production) was significantly attenuated by pretreatment with a neurokinin-1 receptor antagonist (Zhu et al, 2009). The striatal neurokinin-1 receptors are expressed by cholinergic and somatostatin/NPY/NOS interneurons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years it has been demonstrated that apart from classical monoaminergic toxicity, METH induces non-monoaminergic neuronal soma degeneration in the striatum of rodents (Jayanthi et al, 2004(Jayanthi et al, , 2005Zhu et al, 2009). The affected cells have been identified as the GABAergic neurons expressing enkephalin and parvalbumin (Jayanthi et al, 2005;Thiriet et al, 2005).…”
Section: Discussionmentioning
confidence: 99%